Die Nuwe Testament en seksualiteit - H. C. van Zyl (Acta Theologica)
This article deals with sexuality in the New Testament. In a first movement the line of thought is pursued in which sex in the New Testament is presented as something legitimate and enjoyable. Celibacy also comes into focus. In a next movement forbidden practices are highlighted: extra-marital sex, divorce and homosexuality. Although the emphasis falls on sexuality in the New Testament, guidelines for sexual conduct today are proposed too.